PENGGUNAAN APLIKASI AI (ARTIFICIAL INTELLIGENCE) CHATGBT UNTUK MEDIA PEMBELAJARAN BAHASA ARAB - Amrin Mustofa; Syailendra Sabdo Djati PS; Suci Rafi Sari; Rofi Wirawan (At Turots: Jurnal Pendidikan Islam, 2024)
The existence of AI (artificial intelligence) has helped and solved many problems faced by humans, including in the world of learning Arabic. Currently, AI is mostly produced and developed by Western countries, but Islamic countries have become consumers and markets for AI products. If AI is not utilized in various areas of life, including the world of Arabic language learning, then the development of human resources, especially Arabic language experts, will certainly be hampered in the future. Therefore, in the world of Arabic language learning, useArtificial Intelligence It is very necessary for the teaching and learning process to be effective and efficient and to achieve the learning objectives. This is what underlies the discussion of this research. This research uses qualitative methods and the type is library research. In the context of ChatGPT which is part of information technology, it is necessary to briefly discuss IT which provides advantages such as speed, consistency, accuracy and reliability so that the learning process runs well and results are obtained. Fundamentals of AI also provides insight into the basic principles of AI development itself, starting from a problem and working to develop a solution. In general, the presence of ChatGPT as an AI product has recently become very important in the world of learning because it helps teachers and makes their work easier, especially in implementing learning strategies in schools. Even if we can utilize the sophistication of AI, of course it should be operated by humans who have a strong understanding of the basics of learning science in detail and in depth. Technology that is part of a scientific application is independent of the values of its users. This means that the benefits of technology depend on the producers and users of each technology. Islam itself strongly recommends its followers to utilize technology in managing the natural resources that Allah has given to their people. Utilization of artificial technology in the form of chatGPT is an inseparable part of the world of learning to facilitate the teaching and learning process and motivate students to study hard and achieve quality results in the future